MEMPERKUAT PEMAHAMAN ANGGOTA SUNNAH WAL JAMAAH DI KALANGAN SISWA: PERAN LEMBAGA PENDIDIKAN DAN STRATEGI IMPLEMENTASI - Khazri Osman; Siti Salwa Jefri; Nur Maisarah Mohd Yusop; Nur Hafizatul Solehah Norizan (CV. Bunda Ratu, 2026)
Educational institutions play a vital role in fostering students’ understanding of Islamic beliefs amid the widespread availability of religious information through digital media. This study aims to identify measures that relevant authorities may consider and to examine educational approaches to teaching Ahl al-Sunnah wa al-Jama'ah. A qualitative approach was employed through interviews and document analysis involving five purposively selected informants, including students, educators, and individuals engaged in Islamic education. The interview data were analyzed thematically and supported by relevant documents. The findings highlight the importance of strengthening Ahl al-Sunnah wa al-Jama'ah content in the curriculum, involving qualified educators, and organizing complementary activities such as study circles, discussion forums, lectures, and da'wah programs. Integrating formal instruction with non-formal religious activities was found to enhance students’ structured and contextual understanding of Islamic creed. The study concludes that educational institutions and relevant authorities should adopt approaches that address students’ contemporary learning needs.